Risdiplam distributes and increases SMN protein in both the central nervous system and peripheral organs. Issue 6 (29th November 2018) - Poirier, Agnès; Weetall, Marla; Heinig, Katja; Bucheli, Franz; Schoenlein, Kerstin; Alsenz, Jochem; Bassett, Simon; Ullah, Mohammed; Senn, Claudia; Ratni, Hasane; Naryshkin, Nikolai; Paushkin, Sergey; et al.
Abstract: Spinal muscular atrophy (SMA) is a rare, inherited neuromuscular disease caused by deletion and/or mutation of the Survival of Motor Neuron 1 ( SMN1) gene. A second gene, SMN2, produces low levels of functional SMN protein that are insufficient to fully compensate for the lack of SMN1 . Risdiplam (RG7916; RO7034067) is an orally administered, small‐molecule SMN2 pre‐mRNA splicing modifier that distributes into the central nervous system (CNS) and peripheral tissues. To further explore risdiplam distribution, we assessed in vitro characteristics and in vivo drug levels and effect of risdiplam on SMN protein expression in different tissues in animal models. Total drug levels were similar in plasma, muscle, and brain of mice (n = 90), rats (n = 148), and monkeys (n = 24). As expected mechanistically based on its high passive permeability and not being a human multidrug resistance protein 1 substrate, risdiplam CSF levels reflected free compound concentration in plasma in monkeys. Tissue distribution remained unchanged when monkeys received risdiplam once daily for 39 weeks. A parallel dose‐dependent increase in SMN protein levels was seen in CNS and peripheral tissues in two SMA mouse models dosed with risdiplam. These in vitro and in vivo preclinical data strongly suggest that functional SMN protein increases seen in patients' blood following risdiplam treatment should reflect similar increases in functional SMN protein in the CNS, muscle, and other peripheral tissues.